2022
DOI: 10.1371/journal.ppat.1010840
|View full text |Cite
|
Sign up to set email alerts
|

Giardia duodenalis: Flavohemoglobin is involved in drug biotransformation and resistance to albendazole

Abstract: Giardia duodenalis causes giardiasis, a major diarrheal disease in humans worldwide whose treatment relies mainly on metronidazole (MTZ) and albendazole (ABZ). The emergence of ABZ resistance in this parasite has prompted studies to elucidate the molecular mechanisms underlying this phenomenon. G. duodenalis trophozoites convert ABZ into its sulfoxide (ABZSO) and sulfone (ABZSOO) forms, despite lacking canonical enzymes involved in these processes, such as cytochrome P450s (CYP450s) and flavin-containing monoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…Furthermore, a sharp rise in refractory patients has also been documented in India [47]. In vitro studies have illustrated that the induction of resistance to benzimidazole is correlated with β-tubulin mutation, degradation of enzymes involed in glycolysis and arginine metabolism, and reduced mRNA expression of flavohemoglobin [36]. The detailed molecular mechanisms of resistance that lead to 5-nitroimidazole refractory Giardia infection as well as other types of resistance is not completely understood despite substantial efforts with laboratory as well as clinical strains.…”
Section: Current Drug Regimen For Giardiasismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a sharp rise in refractory patients has also been documented in India [47]. In vitro studies have illustrated that the induction of resistance to benzimidazole is correlated with β-tubulin mutation, degradation of enzymes involed in glycolysis and arginine metabolism, and reduced mRNA expression of flavohemoglobin [36]. The detailed molecular mechanisms of resistance that lead to 5-nitroimidazole refractory Giardia infection as well as other types of resistance is not completely understood despite substantial efforts with laboratory as well as clinical strains.…”
Section: Current Drug Regimen For Giardiasismentioning
confidence: 99%
“…Also, this drug is not recommended during pregnancy due to teratogenic effects in animals and may be in humans as well [17]. Trophozoites metabolize albendazole and result in the formation of toxic intermediates: albendazole sulfone and albendazole sulfoxide with the help of flavohemoglobin, a NADH oxidase (gNADHox) present inside the parasite (Figure 1) [36]. It has been established that the albendazole binds to the beta-tubulin of the parasite, and the presence of two amino acids (Glu-198 and Phe-200) in the beta-tubulin sequence renders this protozoan susceptible to benzimidazoles (Table 1).…”
Section: Current Drug Regimen For Giardiasismentioning
confidence: 99%
“…However, as with most of the infectious diseases, the cornerstone therapy for H. pylori in children has long been the traditional triple therapy consisting of the proton pump inhibitors, as well as antibiotics, namely amoxicillin, clarithromycin, and metronidazole that are also known to be the most common amongst drugs employed in the treatment of other bacterial infectious diseases. As such, these anti-infective agents were recorded as one of the most susceptible to microbial resistance [ 197 , 198 , 199 , 200 ]. In addition, the World Health Organization published a new recommendation for treating tuberculosis using a first-line regimen to shorten therapy from six to four months in efforts to reduce prolonged exposure whilst maintaining clinical efficacy [ 201 , 202 ].…”
Section: Currents Trends and Gapsmentioning
confidence: 99%
“…Albendazole, a benzimidazole carbamate, exhibits activity against G. intestinalis , and trophozoites can metabolize this drug into its toxic intermediates: albendazole sulfone and albendazole sulfoxide. The conversion process involves a recently described flavohemoglobin present in the parasite [ 43 ]. Despite the fact that several microtubular structures constitute the parasite’s cytoskeleton, electron microscopy studies have shown that the drug specifically affects the ventral disc ( Figure 6 ) [ 44 ].…”
Section: Compounds Used In the Giardiasis Treatmen...mentioning
confidence: 99%
“…Furthermore, albendazole can potentially interfere with mitotic spindle development during cell division, particularly affecting the G2 phase of the G. intestinalis cell cycle [33]. In vitro studies have demonstrated the ability to induce albendazole resistance, which correlates with beta-tubulin mutation, modulation of enzymes involved in glycolysis and arginine metabolism, and decreased Giardia flavohemoglobin mRNA expression [43,45,46]. peripheral vesicles (P).…”
Section: Albendazolementioning
confidence: 99%